Exploring gender-based psychological profiles in Malaysian sub-elite athletes - Muhammad Noor Hizami Hamidi; Shamsulariffin Samsudin; Hairul Anuar Hashim; Mohd Rozilee Wazir Norjali Wazir; Geok, Soh Kim; Roxana Dev Omar Dev (RSIS International, 2025)
This research investigated gender differences in the psychological profiles of Malaysian sub-elite athletes, concentrating on emotional intelligence, mental toughness, mood states, and sports anxiety. A total of 228 student-athletes (146 men and 82 females) from the Malaysian National Sports School engaged in the study via a cross-sectional survey methodology. Standardized tools were employed to evaluate the specified psychological characteristics, and independent sample t-tests were performed to ascertain gender differences. The results indicated that male athletes exhibited markedly elevated levels of dedication, confidence, and focus, but female athletes had heightened levels of anxiety and concentration disturbance. No notable discrepancies were detected in the aspects of emotional intelligence or in mood states, including wrath and perplexity. The findings underscore gender-specific psychological strengths and weaknesses influenced by cultural expectations, social upbringing, and sports contexts. These observations underscore the necessity for culturally attuned and gender-specific psychological treatments in sports environments to improve athlete performance and mental health. Future study should utilize longitudinal and mixed methods approaches to investigate the developmental trajectories of psychological attributes in varied sports groups.